CDsCuOₓ Nanocomposites for Peroxydisulfate Activation Toward Tetracycline Degradation - Rodríguez, Karin; Andolar, Mina; Hakkarainen, Poul (Journal of Green Energy and Environmental Engineering, 2023)
The construction of abundant active sites and enhancement of pollutant-specific selectivity on heterogeneous catalyst surfaces are crucial for efficient pollutant removal via persulfate-based advanced oxidation processes. The incorporation of carbon dots (CDs) into copper-based oxides to construct multivalent metal species can significantly improve the activation capability of peroxydisulfate (PS). In this study, a simple calcination method is employed to regulate the valence state of Cu in copper-based oxides using CDs, resulting in the synthesis of a CDs/CuO composite with multiphase structures comprising Cu⁰, Cu₂O, and CuO. In the degradation of tetracycline (TC) (used as a model pollutant), the CDs/CuO composite exhibits excellent activation capability. Under the reaction conditions of TC concentration (50 mg/L), PS concentration (0.5 mmol/L), and catalyst concentration (0.06 g/L), the degradation efficiency of TC reaches 99% within 60 min, with an apparent reaction rate constant of 0.066 min⁻¹. This reaction rate is 6.6 times that of pure CuO. Cu⁰ acts as a continuous electron donor, not only inducing the generation of selective singlet oxygen (¹O₂) but, more importantly, promoting the Cu²⁺/Cu⁺ cycle reaction. This cycle generates hydroxyl radicals (·OH) and improves activation efficiency. The use of CDs regulates the coexistence of multivalent Cu active sites in the catalyst, which enhances the activation capability for PS, providing a new idea for the efficient design of catalysts.